Sympatric Pieris butterfly species exhibit a high conservation of chemoreceptors - Wang, Qi; Dicke, Marcel; Haverkamp, Alexander (Frontiers in Cellular Neuroscience, 2023)
Sensory processes have often been argued to play a central role in the selection of ecological niches and in the formation of new species. Butterflies are among the best studied animal groups with regards to their evolutionary and behavioral ecology and thereby offer an attractive system to investigate the role of chemosensory genes in sympatric speciation. We focus on two Pieris butterflies with overlapping host-plant ranges: P. brassicae and P. rapae. Host-plant choice in lepidopterans is largely based on their olfactory and gustatory senses. Although the chemosensory responses of the two species have been well characterized at the behavioral and physiological levels, little is known about their chemoreceptor genes. Here, we compared the chemosensory genes of P. brassicae and P. rapae to investigate whether differences in these genes might have contributed to their evolutionary separation. We identified a total of 130 and 122 chemoreceptor genes in the P. brassicae genome and antennal transcriptome respectively. Similarly, 133 and 124 chemoreceptors were identified in the P. rapae genome and antennal transcriptome. We found some chemoreceptors being differentially expressed in the antennal transcriptomes of the two species. The motifs and gene structures of chemoreceptors were compared between the two species. We show that paralogs share conserved motifs and orthologs have similar gene structures. Our study therefore found surprisingly few differences in the numbers, sequence identities and gene structures between the two species, indicating that the ecological differences between these two butterflies might be more related to a quantitative shift in the expression of orthologous genes than to the evolution of novel receptors as has been found in other insects. Our molecular data supplement the wealth of behavioral and ecological studies on these two species and will thereby help to better understand the role of chemoreceptor genes in the evolution of lepidopterans.